A Pharmacognostic, Phytochemical Study of Godhuma Bija (Triticum Aestivum Linn.) (AYUSHDHARA, 2024)
Background: Godhuma Bija (Triticum aestivum Linn.)are used for various conditions of ailments in traditional systems of medicine since ancient times. Pharmacognostic and phytochemical studies make the drugs more standardized and evidence based. Aims: This study was designed to lay down the various pharmacognostic and phytochemical standards which will be helpful to ensure the purity, safety, and efficacy of this medicinal plant. Materials and Methods: Various methods including macroscopic, microscopic, physicochemical and phytochemical methods were applied to determine the diagnostic features for the identification and standardization of intact and powdered drug of Godhuma Bija (Triticum aestivum Linn.) Results: The shape, colour, odour and surface characteristics were determined for the intact drug and powdered materials of Godhuma Bija (Triticum aestivum Linn.) Light and electron microscope images of cross-section of stamen and powdered microscopy revealed useful diagnostic features. Phytochemical, physicochemical analysis of powdered drug proved useful to differentiate the powdered drug material. High performance thin layer chromatography analysis showed the presence of important phytoconstituents. Conclusion: Morphology as well as various pharmacognostic aspects of Godhuma Bija (Triticum aestivum Linn.) of the plant were studied and have been described here along with phytochemical and physicochemical studies, which will help in authentication and quality control.